Theoretical aspects of the generation of radio noise by the planet Jupiter - Deift, Percy A (Rhodes University, Faculty of Science, Department of Physics, 1972)
Decameter radiation was first observed from Jupiter by Burke and Franklin (JGR 60, 213, 1955). In 1964 Bigg (Nature, 203, 1008, (1964)) found that 1o exerted a profound effect on the radiation. The majority of the early theories to explain the origin of the decameter emissions, attributed the radiation to an emission process occurring at or near the electron gyrofrequency or the plasma frequency. Intro., p. 1. The majority of the early theories to explain the origin of the decameter emissions, attributed the radiation to an emission process occurring at or near the electron gyrofrequency or the plasma frequency (for a review see eg. Warwick, Space Sci. Rev. &" 841 (1967)). More recent work centred around the question of how 10 modulates the emission (see the article of Carr and Gulkis (Annual Review of Astronomy and Astrophysics Vol 8 (1970)) for a detailed review).
Keywords: Jupiter (Planet); Radio astronomy; Radio noise